Years of life lost associated with COVID-19 deaths in the USA during the first year of the pandemic - Quast, Troy (J Public Health (Oxf), 2021)
BACKGROUND: Years of Life Lost (YLLs) measure the shortfall in life expectancy due to a medical condition and have been used in multiple contexts. Previously it was estimated that there were 1.2 million YLLs associated with coronavirus disease 2019 (COVID-19) deaths in the USA through 11 July 2020. The aim of this study is to update YLL estimates for the first full year of the pandemic. METHODS: We employed data regarding COVID-19 deaths in the USA through 31 January 2021 by jurisdiction, gender and age group. We used actuarial life expectancy tables by gender and age to estimate YLLs. RESULTS: We estimated roughly 3.9 million YLLs due to COVID-19 deaths, which correspond to roughly 9.2 YLLs per death. We observed a large range across states in YLLs per 10 000 capita, with New York City at 298 and Vermont at 12. Nationally, the YLLs per 10 000 capita were greater for males than females (136.3 versus 102.3), but there was significant variation in the differences across states. CONCLUSIONS: Our estimates provide further insight into the mortality effects of COVID-19. The observed differences across states and genders demonstrate the need for disaggregated analyses of the pandemic’s effects.